First evaluation of genetic diversity and population structure of Phelsuma inexpectata (Gekkonidae), a critically endangered gecko endemic to Reunion Island - Yann Gomard; Mickaël Sanchez; Margot Caubit; Markus A. Roesch; Alicia Bonanno; Johanna Clémencet (PLoS ONE, 2025)
The Manapany day gecko, Phelsuma inexpectata , is a critically endangered reptile endemic to Reunion Island (Southwestern Indian Ocean region). In the present study, we provide the first in-depth insights into the genetic diversity and population structure of the species across its main geographic range, limited to a narrow 14–km littoral fringe in the south of the island. We used two mitochondrial genes and twenty microsatellite loci to genotype 452 geckos sampled in anthropized and natural sites. Compared to other insular species of the Phelsuma genus, P. inexpectata displays a low genetic diversity with nine mitochondrial haplotypes detected, and based on the nuclear markers, a mean number of alleles ( N a ) of 2.8 ± 0.3, and an observed ( H o ) and expected heterozygosity ( H e ) reaching a maximum of 0.353 ± 0.053 and 0.345 ± 0.046 per site, respectively. For most sites, no significant deviations from Hardy–Weinberg equilibrium were detected. Along the limited distribution of P. inexpectata, isolation-by-distance patterns and geographical population structures were found with low first-generation migrants between sites. Genetic diversity distribution and structure are likely shaped by historical processes, including the fragmentation and isolation of relict populations, and anthropogenic-mediated colonization of novel habitats. The fine-scale population differentiation and genetic structuring, combined with the limited dispersal capacity of P. inexpectata , highlight the vulnerability of local gecko populations to extinction in the face of habitat fragmentation and loss. The low genetic diversity of P. inexpectata could limit its evolutionary potential and make it vulnerable to stochastic changes in its environment. Hence, efforts to conserve the genetic diversity should be strengthened, notably in natural sites harboring an original and remarkable genetic diversity.